Mitochondrial DNA-based genetic diversity of Anopheles nivipes in North East India. (1st November 2016) - Sarma, N. P.; Singh, S.; Sarma, D. K.; Bhattacharyya, D. R.; Kalita, M. C.; Mohapatra, P. K.; Dohutia, C.; Mahanta, J.; Prakash, A.
Abstract: Malaria is a major public health problem in north-east India mainly transmitted by Anopheles baimai and An. minimus while Anopheles nivipes plays an important supportive role. The genetic diversity of An. nivipes in north-east India was investigated by employing two mitochondrial DNA markers namely NADH dehydrogenase 5 (ND5) and cytochrome oxidase sub unit II (COII). High genetic diversity in An. nivipes was observed by the detection of 16 haplotypes among 30 sequences of ND5 gene and 29 haplotypes among 29 COII sequences . Anopheles nivipes of north-east India was significantly differentiated genetically with that of neighboring South-east Asian An. nivipes as revealed by pairwise FST values of 0.127 ( p < 0.01) and 0.044 ( p < 0.001) for ND5 and COII genes, respectively, suggesting geographical barriers to gene flow in this species between the two geographical areas resulting in significant population structuring.